Correction: Early diagnosis of sepsis in emergency departments, time to treatment, and association with mortality: An observational study. - Gunnar Husabø; Roy M Nilsen; Hans Flaatten; Erik Solligård; Jan C Frich; Gunnar T Bondevik; Geir S Braut; Kieran Walshe; Stig Harthug; Einar Hovlid (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0227652.].